PENINGKATAN KETERAMPILAN MENYAMPAIKAN TANGGAPAN MELALUI MODEL TALKING STICK BERBANTUKAN MEDIA GAMBAR PADA SISWA KELAS III - Juwariyah, Juwariyah (JURNAL SINEKTIK, 2020)
The purpose of this research is increasing the competency of imparting the response the Third Grade students of Sambongpayak Elementary School Subdistrict of Gunem of Rembang Regency on the 1st Semester 2019/2020 Year Academic through Model Talking Stick assisted with visual media. This research is a Classroom Action Research (CAR), consist of 2 cycles. The action of this reseach is learning through Model Talking Stick assisted with visual media. The result of this research is Model Talking Stick assisted with visual media increased the competency of imparting the response the Third Grade students of Sambongpayak Elementary School. The competency of imparting the response increased from the class average at 53 with 22% as the completeness into the class average at 78 with 89% as the completeness.